Estimation of Mobile Phone and Computer Waste: A Case Study of Kashmir University, Hazratbal (International Journal of Innovative Research in Engineering & Management, 2022)
Electrical and electronic equipements are  classified as devices that operate on electrical current and  electromagnetic fields. These EEE are transformed into  WEEE after reaching the end of their useful lives. The  usage of electrical and electronic equipment has expanded  quickly, and because of their shorter lifespans, a lot of e waste is produced globally. WEEE production reached  44.7 Mt in 2016 and would reach 52.2 Mt by 2021. The  amount of elements in e-waste, including lead, chromium,  arsenic, cadmium, and others, makes it dangerous for both  the environment and living things. Only the estimation of  mobile phones and personal computers at the University of  Kashmir in J&K is the focus of this study. For that reason,  I anticipate e-waste creation using a modified exponential  equation and utilized the end-of-life model as a basis  model to estimate current e-waste generation. At the  University of Kashmir, a questionnaire survey was  undertaken to learn how consumers dispose of their  electronic devices once they have served their purpose.  The typical life lengths of electronic devices (such as  mobile phones and personal computers) have upper and  lower bounds in two scenarios, respectively. The study's  findings indicated that, in the case of mobile phones, the  total amount of garbage created for 2021 will be close to  313.88 units and might reach as high as 561.57 units by  2025. The total amount of garbage produced under the  lower limit is projected to be 358.15 units in 2021 and to  rise to 599.05 units by 2025. Similar to PCs, the total waste  created by PCs will increase up to 551.08 units by 2025,  from 298.52 units in 2021. The total amount of garbage  produced under a reduced restriction, however, was 325.72  units in 2021 and will rise to 581.84 units by 2025. As a  result, enough infrastructures should be in place to handle  the volume of trash that is produced, and this assessment  can serve as a basis for politicians to express timely  concern and take appropriate action to route e-waste from  its user to disposal.
Keywords: E-waste Generation; Kashmir University; Mobile Waste; Electrical And Electronic Equipment’s